A Zero‐Rank, Maximum Nullity Perfect Electromagnetic Wave Absorber. Issue 8 (28th January 2019) - Suen, Jonathan Y.; Fan, Kebin; Padilla, Willie J.
Abstract: Electromagnetic wave absorbers formed from a metamaterial layer are demonstrated and near‐perfect absorption is realized across much of the spectrum. Alternatively, an unpatterned low‐loss dielectric layer forms an absorber of coherent light and shows near‐zero reflectance and high absorption. The latter is termed a coherent perfect absorber (CPA) and may be described as a time‐reversed laser. Here, a more fundamental system of dielectric metasurfaces is experimentally demonstrated, which may achieve either coherent or incoherent absorption. The absorber is viewed as two CPAs with eigenmodes of opposite symmetry, and may achieve incoherent absorption with a null scattering matrix, or coherent absorption with a rank‐1 scattering matrix. Metasurface absorbers are classified based on their scattering matrix rank and nullity. The demonstrated system and theory establish a path to realize a new class of absorbers useful for future novel applications, including hyperspectral imaging and energy harvesting. Abstract : A more fundamental class of metasurface electromagnetic wave absorber is demonstrated, a two‐port device exhibiting a full‐nullity scattering matrix and exhibiting incoherent absorption due to the degenerate critical coupling of two eigenmodes. This contrasts with coherent perfect absorbers which are shown to have a rank‐1 scattering matrix and exhibit a phase‐dependent absorption, and one‐port ground plane absorbers.